1980
DOI: 10.1002/cd.23219801008
|View full text |Cite
|
Sign up to set email alerts
|

The generalities and specifics of long-term memory in infants and young children

Abstract: How is memory in the first three years of life related to memory in the older child or adult? This is a classic question raised originally by the phenomenon termed infantile amnesia by Freud and later Freudians. Adults and older children do not usually remember incidents from their lives that happen prior to the age of three. For most people the number of memories increases after the age of three and by the school years (seven or eight) becomes a flood of remembered episodes forming an autobiographical history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 9 publications
3
82
0
Order By: Relevance
“…A considerable body of research has shown that children acquire scriptknowledge at a very early age and extract scripts after even a small number of experiences of an event sequence (e.g., Fivush, 1984;Hudson & Nelson, 1986;Nelson, 1986;Nelson & Hudson, 1988;Nelson & Ross, 1980). This may suggest that scripts are good candidates for developmentally early nonperspectival representational frameworks.…”
Section: Nonperspectival Temporal Framework: Scriptsmentioning
confidence: 99%
“…A considerable body of research has shown that children acquire scriptknowledge at a very early age and extract scripts after even a small number of experiences of an event sequence (e.g., Fivush, 1984;Hudson & Nelson, 1986;Nelson, 1986;Nelson & Hudson, 1988;Nelson & Ross, 1980). This may suggest that scripts are good candidates for developmentally early nonperspectival representational frameworks.…”
Section: Nonperspectival Temporal Framework: Scriptsmentioning
confidence: 99%
“…Bühler (1930) pointed out that 2-year-olds sometimes remernher even infrequent events for a long period of time. There are sirnilar reports in more reeent sturlies (e.g., Nelson & Ross, 1980;Todd & Perlmutter, 1980).…”
Section: Memory For Events and Event Sequencesmentioning
confidence: 94%
“…Older subjects were better able to recall objects with changing positions. Nelson and Ross (1980) also used the diary method and determined that toddlers (who had just turned two) employed more intentional memory activities for recall of events than for the location of meaningful objects. The older children were able to recall both objects and events accurately after a relatively long period of time (i.e., up to three months).…”
Section: Retrieval Of Hidden Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundbreaking work conducted by Katherine Nelson and colleagues (Nelson, 1986;Nelson & Gruendel, 1981;Nelson & Ross, 1980) markedly changed this perspective. When asking children to report what usually happens in familiar events such as going to McDonald´s, grocery shopping, or having a birthday party, they found that children as young as three years of age indeed were able to provide accounts of script-like events following a certain structure and order (Nelson, 1986;Nelson & Gruendel, 1981).…”
Section: Introductionmentioning
confidence: 99%